Quality of targeted temperature management and outcome of out-of-hospital cardiac arrest patients: A post hoc analysis of the TTH48 study. (August 2021) - De Fazio, Chiara; Skrifvars, Markus B.; Søreide, Eldar; Grejs, Anders M.; Di Bernardini, Eugenio; Jeppesen, Anni Nørgaard; Storm, Christian; Kjaergaard, Jesper; Laitio, Timo; Rasmussen, Bodil Sten; Tianen, Marjaana; Kirkegaard, Hans; et al.
Abstract: Background: No data are available on the quality of targeted temperature management (TTM) provided to out-of-hospital cardiac arrest (OHCA) patients and its association with outcome. Methods: Post hoc analysis of the TTH48 study (NCT01689077), which compared the effects of prolonged TTM at 33 °C for 48 h to standard 24-h TTM on neurologic outcome. Admission temperature, speed of cooling, rewarming rates, precision (i.e. temperature variability), overcooling and overshooting as post-cooling fever (i.e. >38.0 °C) were collected. A specific score, ranging from 1 to 9, was computed to define the "quality of TTM". Results: On a total of 352 patients, most had a moderate quality of TTM (n = 217; 62% — score 4–6), while 80 (23%) patients had a low quality of TTM (score 1–3) and only 52 (16%) a high quality of TTM (score 7–9). The proportion of patients with unfavorable neurological outcome (UO; Cerebral Performance Category of 3–5 at 6 months) was similar between the different quality of TTM groups (p = 0.90). Although a shorter time from arrest to target temperature and a lower proportion of time outside the target ranges in the TTM 48-h than in the TTM 24-h group, quality of TTM was similar between groups. Also, the proportion of patients with UO was similar between the different quality of TTM groups when TTM 48-h and TTM 24-h were compared. Conclusions: In this study, high quality of TTM was provided to a small proportion of patients. However, quality of TTM was not associated with patients' outcome.